A polymer-based composite material with high thermal conductivity and high insulation
By using modified liquid crystal polymer matrix and surface-modified sheet boron nitride filler in polymer-based composite materials, combined with silicon oxide intermediate layer and alternating electric field induction technology, the problem of insufficient thermal conductivity of fillers in traditional composite materials is solved, and high thermal conductivity and high insulation performance is achieved.
Patent Information
- Application Number
- CN202411913897.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-08
AI Technical Summary
The chemical compatibility between inorganic fillers and organic polymer matrix in traditional polymer matrix materials is poor, and the phonon frequency mismatch leads to high interface thermal resistance and inability to effectively transfer the thermal conductivity of the filler, which limits the thermal conductivity of the composite materials.
The modified liquid crystal polymer matrix and surface-modified sheet boron nitride filler are used to introduce benzene ring or biphenyl rigid chain segments through the esterification reaction to improve the phonon matching performance of the matrix; the silicon oxide intermediate layer is coated on the surface of the filler to optimize the phonon conduction performance and reduce the interface thermal resistance; during the melt blending process, the directional arrangement of the filler is induced by an alternating electric field to build an efficient thermal conduction path.
It significantly improves the thermal conductivity and interface bonding force of the composite material, reduces the interface thermal resistance, enhances the dispersion and directional distribution of the filler, and ensures the stable performance of the composite material in the high temperature range.
Smart Images

Figure CN119775727A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal conductive composite materials, in particular to a polymer-based composite material with high thermal conductivity and high insulation. Background Art
[0002] With the development of high integration and high power of modern microelectronic devices, the size of electronic products has been continuously reduced, while the power density has increased significantly. The heat dissipation problem caused by this has become increasingly prominent, seriously affecting the operating stability and service life of electronic products, and has become one of the technical bottlenecks that urgently need to be broken through. In order to ensure that electronic components can operate stably for a long time, it is particularly important to improve the heat dissipation capacity. Developing materials with high thermal conductivity is a key way to solve this problem.
[0003] In order to improve the thermal conductivity of polymer-based composite materials, inorganic thermal conductive fillers (such as boron nitride, aluminum oxide, etc.) are usually added to the matrix to construct a thermal conductive path. However, due to the poor chemical compatibility between the inorganic filler and the organic polymer matrix, as well as the serious mismatch of the phonon frequency, the interface thermal resistance is too high, and the thermal conductivity of the filler cannot be effectively transferred to the polymer matrix, resulting in limited overall thermal conductivity of the composite material. At the same time, poor interface bonding is also prone to microcracks and peeling, especially during thermal cycling, where interface stress concentration leads to reduced long-term stability of the composite material.
[0004] Traditional filler dispersion technology mainly relies on high shear mixing process to randomly distribute fillers in the matrix. However, for flaky fillers (such as boron nitride), this random distribution method easily leads to filler agglomeration and accumulation, thereby destroying the continuity of the heat conduction path and reducing the overall thermal conductivity efficiency. In addition, the directional arrangement of fillers is difficult to achieve, especially for scenarios with high requirements for in-plane thermal conductivity (such as 5G heat dissipation substrates). The disordered arrangement of fillers will cause the heat conduction path to be interrupted, making the thermal conductivity of the composite material far lower than the theoretical calculated value. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a high thermal conductivity and high insulation polymer-based composite material, which solves the problems of poor chemical compatibility between inorganic fillers and organic polymer matrices in traditional composite materials, severe mismatch of phonon frequencies, excessively high interfacial thermal resistance, and inability to effectively transfer the thermal conductivity of the filler to the polymer matrix, resulting in limited overall thermal conductivity of the composite material.
[0006] To achieve the above objectives, the present invention is implemented by the following technical solution: a polymer-based composite material with high thermal conductivity and high insulation, the composite material comprising the following components in percentage by mass: Modified liquid crystal polymer matrix: 55% to 60%, introducing benzene rings or biphenyl rigid segments through esterification reaction to improve elastic modulus and phonon matching performance; Surface modified boron nitride flake filler: 38% to 43%, filler thickness is 20 to 50 nanometers, diameter is 1 to 5 micrometers, and the surface is coated with a silicon oxide intermediate layer with a coating thickness of 5 to 10 nanometers to optimize phonon conduction performance and reduce interface thermal resistance; Antioxidant: 0.5% to 1.0%, used to improve the heat resistance and environmental stability of the material; Coupling agent: 0.5% to 1.0%, used to enhance the interface bonding between filler and matrix; Other unavoidable impurities: ≤0.1%.
[0007] Furthermore, a modified liquid crystal polymer matrix of 55% to 60% is prepared by the esterification reaction of terephthalic acid and ethylene glycol, and a 10% to 15% by mass percentage of benzene rings or biphenyl rigid chain segments are introduced to enhance the rigidity and phonon conduction performance of the matrix, wherein the benzene rings or biphenyl chain segments are derived from the copolymerization of isophthalic acid or biphenyl diphthalic acid with terephthalic acid, which can effectively improve the elastic modulus of the matrix and the phonon matching performance with the filler; a surface-modified flaky boron nitride filler of 38% to 43% has a thickness of 20 to 50 nanometers and a diameter of 1 to 5 microns, and a silicon oxide intermediate layer is coated on the surface of the filler by a sol-gel method, and the intermediate layer has a thickness of 5 to 10 nanometers, and the coating is prepared by molar polymerization of tetraethoxysilane and water. The material is prepared by preparing a sol in a ratio of 1:4, coating it with a spin coating process, and then calcining it at 400 degrees Celsius, which is used to optimize the phonon conduction performance and reduce the interface thermal resistance, thereby constructing a continuous and efficient thermal conduction path; 0.5% to 1.0% of antioxidant, the antioxidant includes a main antioxidant 1010 or an auxiliary antioxidant 168, which can improve the heat resistance and environmental stability of the material; 0.5% to 1.0% of coupling agent, the coupling agent includes a silane coupling agent KH-550 or a titanate coupling agent NDZ-201, which is used to enhance the interface bonding force between the filler and the matrix, improve the dispersion of the filler and reduce the interface thermal resistance; other unavoidable impurities are ≤0.1% to ensure the stability and purity of the material performance.
[0008] Preferably, the modified liquid crystal polymer matrix is prepared by esterification reaction of terephthalic acid and ethylene glycol, and 10% to 15% by mass of benzene rings or biphenyl segments are introduced to enhance the rigidity and phonon conduction performance of the matrix. The main antioxidant is 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), the auxiliary antioxidant is triphenyl phosphite, and the coupling agent is a silane coupling agent (KH-550).
[0009] Furthermore, terephthalic acid and ethylene glycol are mixed in a molar ratio of 1:1.2, and a linear polymer is formed by an esterification reaction at 180 to 220 degrees Celsius, and 10% to 15% by mass of benzene rings or biphenyl segments are introduced into the molecular chain. These rigid segments are obtained by copolymerizing isophthalic acid or biphenyl diphthalic acid with terephthalic acid. The rigid segments can effectively improve the rigidity and elastic modulus of the liquid crystal polymer matrix, and at the same time optimize the phonon matching performance between the matrix and the filler to improve the thermal conductivity efficiency; the main antioxidant is selected as 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), and its dosage is controlled at 0.5% to 1.0% The range of 1% to 2% can provide excellent long-term thermal stability and antioxidant properties, and prevent the polymer matrix from oxidative degradation under high temperature conditions. The auxiliary antioxidant is triphenyl phosphite (abbreviated as 168), which is used for synergistic effect and further enhances the antioxidant effect by capturing free radicals, thereby extending the service life of the composite material. The coupling agent is silane coupling agent KH-550, and its chemical name is γ-aminopropyltriethoxysilane. The dosage is 0.5% to 1.0%, which can form chemical bonds with flaky boron nitride fillers and liquid crystal polymer matrix through its functional groups, thereby improving the dispersion of fillers in the matrix and the interface bonding force, and further reducing the interface thermal resistance, thereby ensuring that the composite material has excellent comprehensive performance.
[0010] Preferably, the thickness of the flaky boron nitride filler is 20 to 50 nanometers and the diameter is 1 to 5 microns. The coated silicon oxide intermediate layer of the flaky boron nitride filler is prepared by a sol-gel method, and the sol used is a mixture of tetraethoxysilane, ethanol and deionized water in a volume ratio of 1:2:10, and is dried at 80 degrees Celsius and calcined at 400 degrees Celsius to form a dense and uniform coating.
[0011] Furthermore, the coating layer is prepared by a sol-gel method, specifically, tetraethoxysilane (TEOS), anhydrous ethanol and deionized water are mixed in a volume ratio of 1:2:10, stirred at 25 to 30 degrees Celsius for 30 minutes to fully hydrolyze it to form a stable sol, and 0.01 to 0.02 molar concentration of hydrochloric acid is added as a catalyst to further promote hydrolysis and polycondensation reactions, and then the boron nitride filler is ultrasonically dispersed into the sol system for 20 to 30 minutes to ensure uniform dispersion of the filler, and the boron nitride filler is spin-coated. The sol is uniformly coated on the surface of the boron nitride flakes, the spin coating speed is controlled at 500 to 1500 revolutions per minute, the spin coating time is 30 to 60 seconds to ensure the uniformity and density of the coating, and after spin coating, it is pretreated in a drying oven at 80 degrees Celsius to remove the surface solvent, and then calcined at 400 degrees Celsius for 1 to 2 hours to form a dense silicon oxide coating. The coating thickness is controlled at 5 to 10 nanometers to ensure that it optimizes the filler phonon conduction performance and reduces the interface thermal resistance while not affecting the filler's thermal conductivity and electrical insulation performance.
[0012] A method for preparing a high thermal conductivity and high insulation polymer-based composite material comprises the following steps: Filler modification step: coating the surface of the flake boron nitride filler with a silicon oxide intermediate layer, the coating process comprising immersing the filler in a sol mixed with tetraethoxysilane and water, forming a uniform coating by spin coating after ultrasonic dispersion, and calcining at 400 degrees Celsius, with the coating thickness controlled at 5 to 10 nanometers; Matrix modification step: copolymerizing terephthalic acid and ethylene glycol through esterification reaction, and introducing benzene rings or biphenyl segments to increase the elastic modulus of the matrix; Melt blending step: mixing the modified boron nitride filler and the modified liquid crystal polymer matrix in proportion, melt blending at 200 degrees Celsius, a shear rate of 150 revolutions per minute, and a mixing time of 10 minutes; Molding steps: The composite material is molded by hot pressing process at 200 degrees Celsius and 10 MPa.
[0013] Furthermore, in the filler modification step, the flaky boron nitride filler is first subjected to physical screening treatment to control its thickness to 20 to 50 nanometers and its diameter to 1 to 5 microns, and then a silicon oxide intermediate layer is coated on the surface of the screened flaky boron nitride filler. Specifically, tetraethoxysilane (TEOS), anhydrous ethanol and deionized water are mixed in a volume ratio of 1:2:10, and stirred at room temperature for 30 minutes to form a uniform sol, and 0.01 to 0.02 molar concentration of hydrochloric acid is added as a catalyst to accelerate the hydrolysis and polycondensation reaction of the sol, and then the flaky boron nitride filler is ultrasonically dispersed into the sol, and the ultrasonic dispersion time is 20 to 30 minutes to ensure uniform dispersion of the filler, and then the sol is subjected to a spin coating process. The glue is evenly coated on the surface of the flaky boron nitride filler, the spin coating speed is controlled at 500 to 1500 revolutions per minute, and the spin coating time is 30 to 60 seconds to ensure the uniformity and adhesion of the coating. The spin-coated filler needs to be dried in a drying oven at 80 degrees Celsius for 1 hour to remove the solvent, and then calcined in an air atmosphere at 400 degrees Celsius for 1 to 2 hours to form a dense silicon oxide coating. The coating thickness is controlled at 5 to 10 nanometers to significantly improve the interface bonding performance and phonon conduction performance between the filler and the matrix; in the matrix modification step, terephthalic acid and ethylene glycol are mixed in a molar ratio of 1:1.2 through an esterification reaction, and an esterification reaction is carried out at 180 to 220 degrees Celsius to form a linear polyester chain, and by introducing 1 0% to 15% by mass of benzene rings or biphenyl segments are used as rigid monomers for copolymerization modification, and the rigid monomers are derived from isophthalic acid or biphenyl dicarboxylic acid. This modification method can significantly improve the elastic modulus and rigidity of the matrix, and optimize its phonon matching performance with the boron nitride filler; in the melt blending step, the modified boron nitride filler and the modified liquid crystal polymer matrix are mixed in proportion, the mass percentage of the modified liquid crystal polymer matrix is 55% to 60%, the mass percentage of the modified boron nitride filler is 38% to 43%, the mass percentage of the antioxidant 1010 and the mass percentage of the coupling agent KH-550 are 0.5% to 1.0%, and the melt blending is carried out at 200 degrees Celsius, and the shear rate is 1 The material is kneaded in a high-shear mixer at 50 revolutions per minute for 10 minutes to ensure uniform dispersion of the filler in the matrix, and then an alternating electric field is used to induce directional arrangement of the filler, with the frequency of the electric field being 1 kilohertz to 10 kilohertz, so as to construct an efficient thermal conduction path; in the molding step, the blended composite material melt is placed in a hot pressing mold, and a hot pressing process is used for molding at 200 degrees Celsius and 10 MPa pressure for 5 to 10 minutes to obtain a polymer-based composite material with uniform size and dense internal structure. The composite material has both high thermal conductivity and high insulation performance, with a thermal conductivity of more than 9 watts per meter Kelvin, a dielectric strength of not less than 10 kilovolts per millimeter, and can maintain stable performance over a wide temperature range of -40 to 120 degrees Celsius.
[0014] Preferably, in the filler modification step, the sol used is a mixture of tetraethoxysilane, ethanol and deionized water in a volume ratio of 1:2:10, and hydrochloric acid is used as a catalyst. After the preparation is completed, ultrasonic dispersion is performed for 30 minutes.
[0015] Further, tetraethoxysilane (TEOS), anhydrous ethanol and deionized water are mixed in a volume ratio of 1:2:10, wherein tetraethoxysilane is used as a silicon source, anhydrous ethanol is used as a solvent, and deionized water is used as a hydrolyzing agent. At the same time, 0.01-0.02 molar concentration of hydrochloric acid is added as a catalyst to promote the hydrolysis and polycondensation reaction of tetraethoxysilane. The specific operation is to stir at room temperature (25-30 degrees Celsius) for 30-60 minutes to allow the reaction to proceed fully and form a uniform and transparent sol system. The formed sol has good stability and low viscosity, which is convenient for subsequent filler coating treatment. Then, the flaky boron nitride filler is added to the prepared sol, and the mixed system is ultrasonically dispersed for 30 minutes using an ultrasonic dispersion device. The ultrasonic dispersion frequency is controlled at 20 kilohertz to 40 kilohertz, and the power is set to 200 to 300 watts to ensure the uniform distribution of the boron nitride filler in the sol and promote the sol to fully contact the filler surface. At the same time, the ultrasonic treatment can effectively remove the adsorbed impurities and bubbles on the filler surface, improve the coating uniformity and adhesion of the coating, and the obtained dispersion system after the dispersion is completed is used for the subsequent spin coating process or other uniform coating treatment to form a silicon oxide coating with a dense structure and good adhesion.
[0016] Preferably, in the melt blending step, the flake boron nitride filler is arranged along the planar direction in the matrix by inducing an alternating electric field, and the frequency of the electric field is 1 kilohertz to 10 kilohertz.
[0017] Furthermore, the flake boron nitride filler is arranged in the plane direction in the matrix by an alternating electric field induction method. Specifically, the modified liquid crystal polymer matrix and the modified boron nitride filler are mixed uniformly according to the mass ratio during the melt blending process, and then placed in a high shear melt blending device with an electric field control function. The directional arrangement of the filler is achieved by applying an alternating electric field. The electric field frequency is 1 kilohertz to 10 kilohertz, and the electric field strength is controlled at 0.5 kilovolts per centimeter to 2 kilovolts per centimeter. The alternating electric field applies a dipole moment to the flake boron nitride filler through a periodically changing electric field direction, driving the filler to be oriented and arranged in the plane direction, thereby forming a continuous heat conduction path. diameter, and at the same time, the stacking effect between fillers is effectively suppressed under the action of the alternating electric field, further improving the uniformity of filler dispersion, reducing filler agglomeration, and ensuring the consistency and stability of the thermal conductivity of the composite material. In order to ensure the integrity of the thermal conduction path and the electric field induced effect, the melt blending temperature is controlled at 200-220 degrees Celsius, the shear rate is 150 revolutions per minute, and the mixing time is 10-15 minutes. Finally, the filler forms a highly ordered planar orientation structure in the matrix. This arrangement can significantly reduce the thermal cross-sectional impedance in the composite material, and improve the in-plane thermal conductivity and overall thermal management efficiency of the composite material.
[0018] Preferably, during the spin coating process of applying a uniform coating, the spin coating speed is controlled at 500 to 1500 revolutions per minute, and the spin coating time is 30 to 60 seconds to ensure uniform coating thickness and good adhesion.
[0019] Furthermore, in the process of spin coating a uniform coating, a spin coating process is used to evenly coat the prepared sol on the surface of the boron nitride flaky filler. Specifically, the boron nitride filler is placed on the sample plate of the spin coating device, and the filler is ensured to be stably fixed in the vacuum adsorption mode, and then the spin coating equipment is gradually started to achieve uniform coating. The spin coating speed is controlled at 500 to 1500 revolutions per minute, wherein the initial low-speed stage (500 to 800 revolutions per minute, lasting 10 to 15 seconds) is used to ensure that the sol fully infiltrates the filler surface, and then the spin coating speed is increased to 1000 to 1500 revolutions per minute and maintained for 20 to 45 seconds to form a uniform and dense coating. During the spin coating process, the coating thickness is mainly controlled by the spin coating speed and time, and is also affected by the viscosity of the sol and the evaporation rate of the solvent. By adjusting the viscosity of the sol (about 1 In addition, in order to further improve the adhesion and uniformity of the coating, the surface of the flaky boron nitride filler is pretreated before spin coating, including drying at 100 degrees Celsius for 30 minutes to remove surface moisture and impurities, and ultrasonic cleaning is used to remove particulate contaminants on the surface of the filler. After the spin coating, the coated filler is immediately placed in a drying oven at 80 degrees Celsius for preliminary drying to remove residual solvent, and then calcined at 400 degrees Celsius for 1 to 2 hours to form a dense and well-adhesive silicon oxide coating. The thickness of the formed coating is uniform and stable, and is controlled in the range of 5 to 10 nanometers, thereby significantly improving the interface bonding performance of the filler and the compatibility with the matrix, and optimizing the thermal conductivity and electrical insulation properties of the composite material.
[0020] Preferably, in the molding step, the hot pressing molding pressure is controlled at 8 to 12 MPa, and the molding time is 5 to 15 minutes to ensure that the filler inside the composite material is evenly distributed and the interface is tightly bonded.
[0021] Furthermore, in the molding step, a hot pressing process is used to mold the melt-blended polymer-based composite material, specifically, the blended composite material melt is placed in a hot pressing mold, and a hot pressing pressure of 8 to 12 MPa is applied in the mold and the molding time is controlled to be 5 to 15 minutes to achieve dense molding of the composite material and ensure the uniform distribution of the filler inside it, wherein the molding temperature is controlled at 200 to 220 degrees Celsius, which is close to the melting temperature range of the polymer matrix, thereby ensuring that the matrix maintains good fluidity during the molding process, and at the same time, the surface-modified flake boron nitride filler can maintain its oriented arrangement structure in the matrix and form a continuous heat conduction path; during the pressure application process, the hot pressing mold adopts a high-precision polished cavity to reduce the molding process. In addition, in order to further optimize the interface bonding performance between the filler and the matrix, the mold needs to be fully preheated before molding to prevent the temperature difference of the material in the mold from causing shrinkage or stress concentration leading to interface stratification; after molding, the composite material needs to be slowly cooled to room temperature to release internal residual stress. At the same time, natural cooling or programmed temperature control cooling is used to ensure the dimensional stability and structural integrity of the composite material. Finally, a high thermal conductivity and high insulation polymer-based composite material with uniform size, uniform internal filler distribution and tight interface bonding is obtained. Its thermal conductivity, mechanical strength and electrical insulation properties all meet the requirements of high-performance applications and are suitable for electronic packaging, new energy thermal management and 5G communication heat dissipation.
[0022] Preferably, in the melt blending step, the mixed material needs to be dried in a vacuum drying oven at 100 to 150 degrees Celsius for 2 to 4 hours to remove volatile impurities and moisture in the material.
[0023] Furthermore, the mixed material needs to be subsequently dried, specifically by transferring the mixed polymer-based composite material melt to a special container and placing it in a vacuum drying oven at a temperature of 100 to 150 degrees Celsius for 2 to 4 hours to remove volatile impurities and moisture in the material. The vacuum degree in the drying oven needs to be maintained between 0.05 and 0.1 MPa to ensure that the volatile components can be efficiently removed under low temperature conditions, thereby avoiding damage to the matrix and filler interface caused by high temperature, and ensuring that the material remains uniform during the drying process; the material needs to be preliminarily screened before drying to remove parts that are not fully mixed or areas where there are obvious filler agglomerations. During the drying process, the material needs to be spread flat on the drying oven tray with a layer thickness of 10 to 15 mm to ensure that the heat and vacuum environment can act evenly on the surface and inside of the material. At the same time, slow heating is used to prevent the material from being heated too quickly, resulting in thermal stress accumulation or rapid release of volatiles, which may cause changes in the material structure. After drying, the dried material needs to be slowly cooled to room temperature to release internal stress, and the necessary rheological properties and dispersion tests should be performed on the material to ensure that the content of moisture and volatile impurities is less than 0.1%, thereby ensuring the stability of the composite material, the dispersion of the filler and its cross-sectional bonding effect, and providing a homogenized and purified material basis for subsequent compression molding.
[0024] Preferably, the calcined flaky boron nitride filler needs to be screened to ensure uniform distribution of filler size, and the particle diameter deviation is controlled within ±10%. The screening uses airflow screening equipment or ultrasonic vibration screening equipment, wherein the airflow screening equipment is suitable for fillers with a smaller particle size range, and the ultrasonic vibration screening equipment is suitable for fillers with a larger particle size. Both ensure screening efficiency and uniformity of particle distribution.
[0025] Furthermore, the calcined flake boron nitride filler needs to undergo strict screening treatment to ensure that the filler size distribution is uniform and the particle diameter deviation is controlled within ±10%. Specifically, the calcined flake boron nitride filler is first cooled to room temperature and graded using airflow screening equipment or ultrasonic vibration screening equipment. The airflow screening equipment is suitable for fillers with a smaller particle size range (diameter between 1 and 3 microns). The screening process separates fillers of different particle sizes according to the airflow velocity through the shearing effect of high-speed airflow to achieve precise particle size control and avoid filler breakage or agglomeration that may be caused by traditional mechanical screening. For fillers with larger particle sizes (diameter between 3 and 5 microns), ultrasonic vibration screening equipment is used to drive the filler movement through the vertical and horizontal vibrations generated by the high-frequency vibration of ultrasonic waves on the screen, thereby effectively separating large particles and small particles, while reducing the blockage and stacking of fillers during the screening process, and improving screening efficiency and particle size distribution. Accuracy; During the screening process, the working air pressure of the airflow screening equipment is controlled at 0.1-0.3 MPa, the airflow velocity is 5-20 meters per second, and the screening time is 10-30 minutes. The vibration frequency of the ultrasonic vibration screening equipment is set to 20,000-40 kHz, and the screening time is 15-30 minutes. The fillers after screening need to be classified and collected according to the target particle size range, and the screening effect is tested by a laser particle size analyzer to ensure that the particle size distribution of the filler after the final screening meets the design requirements, and the particle diameter deviation is controlled within ±10% to ensure the uniformity of dispersion and effectiveness of orientation arrangement of the filler in the subsequent composite material. At the same time, the filler after screening needs to be placed in a vacuum drying oven at 100-120 degrees Celsius for secondary drying for 2-3 hours to remove moisture and impurities that may be introduced during the screening process, and further improve the purity and performance stability of the filler, thereby ensuring that the thermal conductivity and interface bonding quality of the composite material meet the expected standards.
[0026] The present invention provides a polymer-based composite material with high thermal conductivity and high insulation, which has the following beneficial effects: 1. The present invention adopts a technical solution of coating a silicon oxide intermediate layer on the surface of a flaky boron nitride filler, prepares a uniform and dense silicon oxide coating by a sol-gel method, and optimizes the coating thickness to within 5 to 10 nanometers by a spin coating process and high-temperature calcination, thereby ensuring that the interface performance and phonon conduction performance of the filler surface are significantly improved; compared with the technical solution of simply mechanically treating or chemically treating the filler in the prior art, the present invention solves the problems of insufficient interface matching between the filler and the polymer matrix and large interface thermal resistance, significantly improves the dispersibility and interface bonding strength of the filler, and thus reduces the interface thermal resistance of the composite material.
[0027] 2. The present invention adopts an alternating electric field induction method to apply a dipole moment to the flaky boron nitride filler through the action of the electric field in the melt blending step, so that it forms an ordered oriented structure along the planar direction in the polymer matrix, thereby constructing an efficient thermal conduction path; compared with the technical solution in the prior art that only relies on shear force to achieve filler dispersion, the present invention solves the problems of uneven orientation of the filler in the matrix and insufficient thermal conductivity due to filler agglomeration, significantly improves the directional distribution of the filler and the continuity of the heat conduction path, and at the same time reduces the thermal impedance effect in the heat conduction path, so that the thermal conductivity of the composite material in the plane is significantly better than that of the prior art.
[0028] 3. The present invention further removes volatile impurities and moisture in the material by adding a 100-150 degree Celsius vacuum drying step to the composite material after melt blending, and combines the screening step of flaky boron nitride filler to accurately control the filler particle size distribution through airflow screening equipment or ultrasonic vibration screening equipment, so that the particle diameter deviation is controlled within ±10%. Compared with the process in the prior art that ignores the drying and screening accuracy, the present invention solves the problem of unstable material performance caused by uneven filler distribution, residual impurities and microscopic defects, significantly improves the environmental adaptability and long-term use stability of the composite material, and ensures that the composite material has stable performance within the operating temperature range of -40 to 120 degrees Celsius. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Please see attached Figure 1 : Example 1: Example with innovative ingredients and process parameters within range values Step 1: Filler modification Flake boron nitride (30 nanometers thick, 3 micrometers in diameter) was placed in a sol, which was a mixture of tetraethoxysilane (TEOS), anhydrous ethanol and deionized water in a volume ratio of 1:2:10, and 0.02 molar hydrochloric acid was added as a catalyst. After stirring for 30 minutes, the boron nitride filler was added and ultrasonically dispersed for 30 minutes (frequency 30 kHz, power 250 watts). The sol was then evenly coated on the surface of the boron nitride by spin coating at a speed of 1000 rpm and a spin coating time of 40 seconds. After coating, it was dried at 80°C for 1 hour and then calcined at 400°C for 1.5 hours to form an 8-nanometer thick silicon oxide coating.
[0032] Step 2: Matrix modification The modified liquid crystal polymer matrix was prepared by using terephthalic acid and ethylene glycol in a molar ratio of 1:1.2 for esterification reaction at a reaction temperature of 200°C and introducing 15% by mass of isophthalic acid as a rigid segment.
[0033] Step 3: Melt Blending The modified liquid crystal polymer (57%) was mixed with silicon oxide-coated boron nitride (41%), antioxidant 1010 (0.6%) and coupling agent KH-550 (0.6%), and high shear melt blended at 200°C, a shear rate of 150 rpm, and mixed for 10 minutes. At the same time, an alternating electric field (frequency 5000 Hz) was applied to induce the boron nitride sheets to align along the planar direction.
[0034] Step 4: Hot Pressing The mixed material was placed in a hot pressing mold, hot pressed at 200° C. and 10 MPa pressure for 10 minutes, and slowly cooled to room temperature to obtain a composite material.
[0035] Summary of Examples In this embodiment, a composite material is prepared by reasonable component design and optimized process parameters. The filler is evenly dispersed, the directional arrangement is good, the interface bonding force is high, and the heat conduction path is continuous. The final composite material has a thermal conductivity of 9.2 W / m·K and a dielectric strength of 12.3 kV / mm, and has good long-term stability.
[0036] Example 2: Example with ingredients and process parameters below the range values Step 1: Filler modification Flake boron nitride (50 nanometers thick, 5 micrometers in diameter) was placed in a sol, which was a mixture of TEOS, ethanol and deionized water in a volume ratio of 1:1:8. A 0.01 molar concentration of hydrochloric acid catalyst was added. After stirring for 15 minutes, ultrasonic dispersion was performed for 20 minutes (frequency 20 kHz, power 200 W), spin coating speed 500 rpm, spin coating time 30 seconds, drying for 50 minutes after coating, calcination temperature 350°C, time 1 hour, to form a 4 nanometer thick silicon oxide coating.
[0037] Step 2: Matrix modification Terephthalic acid and ethylene glycol were esterified in a 1:1 molar ratio at a reaction temperature of 180°C, and 8% by mass of isophthalic acid was introduced as a rigid segment.
[0038] Step 3: Melt Blending Modified liquid crystal polymer (53%), boron nitride filler (44%), antioxidant 1010 (0.3%), and coupling agent KH-550 (0.3%) were mixed and melt-blended at 190°C under high shear, with a shear rate of 120 rpm and mixing for 5 minutes without electric field induction.
[0039] Step 4: Hot Pressing The hot pressing pressure is 6 MPa, the molding time is 5 minutes, and the molding is carried out by rapid cooling.
[0040] Summary of Examples Since the component content and process parameters are lower than the range value, the filler coating is not dense enough, the proportion of matrix rigid segments is insufficient, the interface bonding force is poor, the filler is arranged in a non-directional manner, the thermal conductivity of the composite material is only 7.0 W / m·K, the interface bonding strength is reduced, and the performance is significantly lower than that of Example 1.
[0041] Example 3: Example with ingredients and process parameters above the range values Step 1: Filler modification Flake boron nitride (thickness 20 nanometers, diameter 1 micron) was placed in a sol, which was mixed with TEOS, ethanol and deionized water in a volume ratio of 1:3:15, and 0.03 mol hydrochloric acid was added. After stirring for 1 hour, ultrasonic dispersion was performed for 40 minutes (frequency 40 kHz, power 300 W), spin coating speed 1500 rpm, spin coating time 60 seconds, drying for 2 hours, calcination temperature 450°C, time 2 hours, and coating thickness 12 nanometers.
[0042] Step 2: Matrix modification Terephthalic acid and ethylene glycol were esterified in a molar ratio of 1:1.5, the reaction temperature was 220°C, and 20% by mass of biphenyl dicarboxylic acid was added.
[0043] Step 3: Melt Blending Modified liquid crystal polymer (60%), boron nitride filler (38%), antioxidant 1010 (0.8%), and coupling agent KH-550 (0.8%) were mixed and high shear melt blended at 220°C, a shear rate of 200 rpm, mixing for 15 minutes, and an electric field frequency of 8000 Hz.
[0044] Step 4: Hot Pressing The hot pressing pressure is 15 MPa, the molding time is 15 minutes, and the molding is performed by slow cooling.
[0045] Summary of Examples Parameters above the range result in excessively thick coatings, excessive substrate rigidity, aggravated filler accumulation, decreased thermal path efficiency, a material thermal conductivity of 8.5 W / m·K, improved cross-sectional bonding strength, but inferior overall performance to Example 1.
[0046] Comparative Experimental Design Comparative Example 1: Lack of silicon oxide coating Process: The boron nitride filler was not modified with a silicon oxide coating and was directly melt blended. The rest of the process was the same as in Example 1.
[0047] Results: The thermal resistance of the interface between the uncoated filler and the substrate increased significantly, the filler was unevenly dispersed, and the thermal conductivity of the composite material was 6.8 W / m·K.
[0048] Comparative Example 2: Lack of matrix rigid segments Process: No benzene ring or biphenyl chain segment was introduced to modify the matrix, and the rest of the process was the same as in Example 1.
[0049] Results: The phonon matching between the matrix and the filler is poor, the elastic modulus is insufficient, the cross-sectional bonding is poor, and the thermal conductivity is 7.1 W / m·K.
[0050] Comparative Example 3: Preparation by Traditional Process Process: No electric field induced filler alignment, low shear mixing (shear rate 100 rpm), and the rest is the same as Example 1.
[0051] Results: The fillers were randomly distributed, the thermal conduction path was discontinuous, and the thermal conductivity was only 6.5 W / m·K.
[0052] Experiment 1: Surface modification experiment of flake boron nitride filler Experimental Description This experiment aims to modify the surface of flake boron nitride filler with silicon oxide coating by sol-gel method to optimize the interface bonding performance between filler and substrate, reduce the interface thermal resistance, and improve the thermal conductivity and dispersibility of the material. The focus of the experiment is to explore the influence of coating thickness uniformity, adhesion and calcination conditions on the filler modification effect.
[0053] Experimental procedures Sol preparation Tetraethoxysilane (TEOS), anhydrous ethanol and deionized water were mixed in a volume ratio of 1:2:10, 0.02 mol hydrochloric acid was added as a catalyst, and the mixture was stirred at room temperature (25°C) for 30 minutes until a uniform and transparent sol was formed.
[0054] Boron Nitride Filler Pretreatment The boron nitride flakes (thickness 30 nm, diameter 3 μm) were dried at 80 °C for 2 h to remove moisture and impurities, and ultrasonic cleaning (frequency 30 kHz, time 10 min) was used to remove surface particle contaminants.
[0055] Filler dispersion The dried boron nitride filler was added into the sol at a mass fraction of 30%, and the system was dispersed for 30 minutes using an ultrasonic dispersion device (frequency 30 kHz, power 250 W) to make the boron nitride particles evenly dispersed in the sol.
[0056] Spin coating The dispersed sol was evenly coated on the surface of the boron nitride filler using a spin coating device. The initial spin coating speed was 500 rpm for 15 seconds to ensure sol wetting, and then increased to 1000 rpm and maintained for 25 seconds to form a uniform coating.
[0057] Drying and calcination The coated boron nitride filler was placed in a drying oven at 80° C. for 1 hour and then transferred to a high-temperature furnace at 400° C. for calcination for 1.5 hours to remove the solvent and organic components and form a dense silicon oxide coating.
[0058] Experimental data Table 1: Experimental data of coating uniformity and interface bonding performance of modified fillers Sample No. Coating thickness (nm) Coating uniformity deviation (%) Cross-sectional bonding strength (MPa) Thermal impedance (K·cm² / W) Dispersion stability (hours) Sample A 6.5 8.3 9.2 1.05 7.5 Sample B 8.0 6.2 10.5 0.98 8.2 Sample C 10.2 11.7 8.7 1.22 7.0 Sample D 4.3 18.5 6.5 1.45 5.3 Sample E 9.8 9.1 9.5 1.15 7.8 Summary and mechanism analysis It can be seen from the experimental data that when the thickness of the silicon oxide coating is in the range of 5 to 10 nanometers (samples B and E), the interface bonding strength and dispersion stability reach a high level, and the thermal impedance is significantly reduced, showing good interface performance. This result shows that when the coating thickness is moderate, it can fully cover the surface of the filler to enhance the interface bonding force without increasing the thermal impedance too much. When the coating thickness is too thin (sample D), the coating does not provide sufficient protection for the filler, and the interface bonding strength and dispersion stability decrease; when the coating is too thick (sample C), the thermal impedance increases significantly and the interface thermal conductivity efficiency decreases.
[0059] Dispersion stability is greatly affected by coating adhesion. The uniform and dense silicon oxide coating enhances the dispersion of fillers in the solution system, and further improves the dispersion effect of subsequent composite materials and the continuity of heat conduction paths by reducing the probability of filler agglomeration. This result is consistent with the previous theoretical analysis of coating thickness and interface performance, verifying the important role of coating thickness in optimizing material performance.
[0060] Experiment 2: Effect of different calcination conditions on the properties of the surface coating of flake boron nitride fillers Experimental Description This experiment studied the effect of calcination temperature and time on the performance of silicon oxide coating on the surface of flake boron nitride, focusing on the changes in the density of the coating, the interfacial bonding force and the dispersion stability of the filler. This experiment adjusted the calcination temperature (350℃, 400℃, 450℃) and calcination time (1 hour, 1.5 hours, 2 hours) to analyze the effect of these conditions on the uniformity of coating thickness and thermal impedance, aiming to optimize the coating formation process and improve the interface performance of the filler.
[0061] Experimental procedures Sol preparation and coating The same sol formula (TEOS: ethanol: deionized water = 1:2:10, catalyst HCl concentration 0.02 mol) as in Experiment 1 was used and stirred at room temperature for 30 minutes to form a transparent sol. The flake boron nitride filler was dried at 80 ° C for 2 hours, then added to the sol at a mass fraction of 30%, ultrasonically dispersed (frequency 30 kHz, time 30 minutes), and coated by spin coating at a speed of 1000 rpm for 40 seconds to obtain a uniform silicon oxide coating.
[0062] Drying and calcination After drying the coated filler at 80°C for 1 hour, the filler was calcined at 350°C, 400°C, and 450°C for 1 hour, 1.5 hours, and 2 hours, respectively, to complete the formation of the silicon oxide coating. During the calcination process, the heating rate was controlled at 5°C / minute to ensure the stability of the coating formation.
[0063] Performance Testing The thickness, uniformity deviation, interface bonding strength, thermal impedance and dispersion stability of the coating after calcination were tested. The coating thickness was measured by scanning electron microscopy (SEM), the interface bonding strength was tested by a tensile testing machine, the thermal impedance was measured by laser flash method, and the dispersion stability was measured by the static dispersion system to determine the filler sedimentation time.
[0064] Experimental data Table 2: Experimental data on the effect of calcination conditions on the performance of silicon oxide coatings Calcination conditions (temperature / time) Coating thickness (nm) Coating uniformity deviation (%) Cross-sectional bonding strength (MPa) Thermal impedance (K·cm² / W) Dispersion stability (hours) 350℃ / 1 hour 4.2 19.2 6.3 1.47 4.5 350℃ / 1.5 hours 6.0 15.8 7.8 1.32 5.9 400℃ / 1.5 hours 8.1 6.3 10.5 0.97 8.4 400℃ / 2 hours 9.0 8.0 9.8 1.12 8.0 450℃ / 1.5 hours 9.5 10.7 9.2 1.15 7.5 450℃ / 2 hours 11.8 14.5 8.7 1.35 6.8 Summary and mechanism analysis The calcination temperature and time have a significant effect on the performance of the silicon oxide coating. Appropriate temperature (such as 400°C) and time (such as 1.5 hours) can achieve the best density of the coating, while the thickness, uniformity and interface bonding strength of the coating show a good balance. When the temperature is low (350°C) or the calcination time is insufficient, the silicon oxide coating is not fully formed, resulting in insufficient coating thickness and poor uniformity (coating uniformity deviation is as high as 19.2%), low interface bonding strength (6.3MPa), and significantly increased thermal impedance. This is mainly due to the failure of the coating structure to be completely cross-linked and the large number of surface defects.
[0065] When the calcination temperature is increased to 450°C, the density of the coating is further improved, but the coating thickness gradually increases (11.8 nanometers), and the uniformity deviation also increases (14.5%), resulting in an increase in the interface thermal resistance (1.35K·cm² / W). This phenomenon can be explained by the thermal expansion effect of the coating. Excessively high temperatures can cause uneven expansion and contraction of silicon oxide during the calcination process, resulting in microcracks and internal stress, which reduces the interface bonding performance and dispersion stability of the coating.
[0066] The optimized calcination conditions (400°C, 1.5 hours) can balance the thickness and uniformity of the coating, while reducing the interfacial thermal resistance (0.97K·cm² / W) and improving the interfacial bonding strength (10.5MPa). This effect comes from the formation of the network structure of the coating at a suitable temperature, complete thermal decomposition and smooth surface, which reduces the phonon scattering effect, optimizes the role of the coating in the phonon conduction path, and enhances the bonding force between the coating and the filler surface, which helps to improve the overall thermal conductivity and dispersion stability of the subsequent composite material. The experimental results verify the necessity and effectiveness of controlling the coating thickness and uniformity to optimize the filler performance.
[0067] Experiment 3: Effect of alternating electric field on filler orientation and thermal conductivity Experimental Description This experiment studies the effect of the frequency of the alternating electric field on the orientation of boron nitride flake fillers in the polymer matrix and the thermal conductivity of the composite material. By changing the electric field frequency (1, 5, 10 kHz), the orientation of the filler, the continuity of the thermal conduction path, and the change law of the interfacial thermal resistance are analyzed, so as to optimize the electric field induction conditions to maximize the thermal conductivity.
[0068] Experimental procedures Filler preparation The silicon oxide coated boron nitride filler (8 nm in thickness and 3 μm in diameter) prepared in Experiment 1 was used with a mass fraction of 41%.
[0069] Matrix modification Terephthalic acid and ethylene glycol were esterified at a molar ratio of 1:1.2, and 15% by mass of isophthalic acid was introduced as a rigid segment to prepare a modified liquid crystal polymer matrix with a matrix mass fraction of 57%.
[0070] Melt Blending Modified boron nitride filler, modified liquid crystal polymer matrix, antioxidant 1010 (mass fraction 0.6%) and coupling agent KH-550 (mass fraction 0.6%) were mixed and high shear melt blended (shear rate 150 rpm) at 200°C for 10 minutes. During the process, alternating electric fields of 1000 Hz, 5000 Hz and 10 kHz were applied to induce the filler to align along the plane of the matrix.
[0071] Hot Press Forming The blended composite material was placed in a hot pressing mold and hot pressed at 200°C and 10 MPa for 10 minutes, and then slowly cooled to room temperature.
[0072] Performance Testing The in-plane thermal conductivity, interfacial thermal resistance, filler orientation and mechanical properties of the composite materials were tested. The thermal conductivity was tested by laser flash method, the interfacial thermal resistance was measured by heat flow meter, the filler orientation was analyzed by scanning electron microscope (SEM), and the mechanical properties were measured by tensile testing machine.
[0073] Experimental data Table 3: Experimental data on the effects of different electric field frequencies on filler orientation and material properties Electric field frequency (kHz) In-plane thermal conductivity (W / m·K) Interface thermal resistance (K·cm² / W) Deviation of filler orientation angle (°) Tensile strength (MPa) Dielectric strength (kV / mm) 1 7.6 1.12 17.5 85.2 11.5 5 9.4 0.95 6.8 91.7 12.4 10 8.2 1.05 12.2 88.4 12.0 Summary and mechanism analysis Experimental data show that different electric field frequencies have a significant effect on the orientation of flake boron nitride fillers and the thermal conductivity of composite materials. When a 1000 Hz electric field is applied, the orientation angle of the filler is large (17.5°), and the thermal conductivity path is not evenly distributed, resulting in a low in-plane thermal conductivity (7.6W / m·K) and a high interface thermal resistance (1.12K·cm² / W). This is mainly due to the insufficient effect of the low-frequency electric field on the dipole moment of the filler, which cannot completely drive the filler to align along the plane direction. The filler is distributed relatively randomly in the matrix, and the continuity of the heat conduction path is limited.
[0074] When the electric field frequency is increased to 5000 Hz, the orientation angle deviation of the filler is significantly reduced (6.8°), the in-plane thermal conductivity is increased to 9.4W / m·K, and the interface thermal resistance is reduced to 0.95K·cm² / W, indicating that the medium-frequency alternating electric field can effectively regulate the orientation of the filler and achieve efficient heat conduction path construction. The mechanism is that the medium-frequency electric field can provide a stable and sufficiently strong dipole moment effect, making the directional arrangement of the flaky filler more orderly, while reducing the phenomenon of filler stacking and random distribution, and improving the heat transfer efficiency between fillers.
[0075] When the electric field frequency is further increased to 10 kHz, although the dipole moment effect is stronger, the high-frequency electric field may cause the filler to vibrate unstably during the arrangement process, the interaction between the fillers is enhanced, local stacking occurs, the orientation angle deviation increases to 12.2°, the interface thermal resistance increases slightly (1.05K·cm² / W), and the in-plane thermal conductivity decreases to 8.2W / m·K. This phenomenon indicates that excessively high frequencies may destroy the stability of the filler arrangement and cause the continuity of the heat conduction path to be weakened.
[0076] From a mechanistic point of view, filler orientation has an important influence on the thermal conductivity of composite materials. According to phonon conduction theory, the more orderly the filler arrangement, the higher the continuity of the thermal conduction path, and the smaller the phonon scattering effect, thereby reducing the interfacial thermal resistance and improving the thermal conductivity efficiency. Medium-frequency (such as 5000 Hz) electric fields can provide the best orientation regulation effect, thereby balancing the filler orientation, thermal conduction path continuity and interface performance, significantly improving the thermal conductivity and mechanical properties of composite materials, and verifying the necessity and effectiveness of alternating electric field frequency optimization.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A polymer-based composite material with high thermal conductivity and high insulation, characterized in that: The composite material comprises the following components in percentage by weight: Modified liquid crystal polymer matrix: 55% to 60%, introducing benzene rings or biphenyl rigid segments through esterification reaction to improve elastic modulus and phonon matching performance; Surface modified boron nitride flake filler: 38% to 43%, filler thickness is 20 to 50 nanometers, diameter is 1 to 5 micrometers, and the surface is coated with a silicon oxide intermediate layer with a coating thickness of 5 to 10 nanometers to optimize phonon conduction performance and reduce interface thermal resistance; Antioxidant: 0.5% to 1.0%, used to improve the heat resistance and environmental stability of the material; Coupling agent: 0.5% to 1.0%, used to enhance the interface bonding between filler and matrix; Other unavoidable impurities: ≤0.1%.
2. A polymer-based composite material with high thermal conductivity and high insulation according to claim 1, characterized in that: The modified liquid crystal polymer matrix is prepared by esterification reaction of terephthalic acid and ethylene glycol, and 10% to 15% by mass of benzene rings or biphenyl segments are introduced to enhance the rigidity and phonon conduction performance of the matrix. The main antioxidant is 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), the auxiliary antioxidant is triphenyl phosphite, and the coupling agent is a silane coupling agent (KH-550).
3. A polymer-based composite material with high thermal conductivity and high insulation according to claim 1, characterized in that: The thickness of the flaky boron nitride filler is 20 to 50 nanometers and the diameter is 1 to 5 micrometers. The coated silicon oxide intermediate layer of the flaky boron nitride filler is prepared by a sol-gel method. The sol used is a mixture of tetraethoxysilane, ethanol and deionized water in a volume ratio of 1:2:10, and is dried at 80 degrees Celsius and then calcined at 400 degrees Celsius to form a dense and uniform coating.
4. A method for preparing a high thermal conductivity and high insulation polymer-based composite material, applied to a high thermal conductivity and high insulation polymer-based composite material according to claims 1-3, characterized in that: The following steps are involved: Filler modification step: coating the surface of the flake boron nitride filler with a silicon oxide intermediate layer, the coating process comprising immersing the filler in a sol mixed with tetraethoxysilane and water, forming a uniform coating by spin coating after ultrasonic dispersion, and calcining at 400 degrees Celsius, with the coating thickness controlled at 5 to 10 nanometers; Matrix modification step: copolymerizing terephthalic acid and ethylene glycol through esterification reaction, and introducing benzene rings or biphenyl segments to increase the elastic modulus of the matrix; Melt blending step: mixing the modified boron nitride filler and the modified liquid crystal polymer matrix in proportion, melt blending at 200 degrees Celsius, a shear rate of 150 revolutions per minute, and a mixing time of 10 minutes; Molding steps: The composite material is molded by hot pressing process at 200 degrees Celsius and 10 MPa.
5. A method for preparing a high thermal conductivity and high insulation polymer-based composite material according to claim 4, characterized in that: In the filler modification step, the sol used is a mixture of tetraethoxysilane, ethanol and deionized water in a volume ratio of 1:2:10, and hydrochloric acid is used as a catalyst. After preparation, ultrasonic dispersion is performed for 30 minutes.
6. A method for preparing a high thermal conductivity and high insulation polymer-based composite material according to claim 4, characterized in that: In the melt blending step, the flake boron nitride filler is arranged along the plane direction in the matrix by inducing an alternating electric field, and the frequency of the electric field is 1 kilohertz to 10 kilohertz.
7. A method for preparing a high thermal conductivity and high insulation polymer-based composite material according to claim 4, characterized in that: During the spin coating process of coating a uniform coating, the spin coating speed is controlled at 500 to 1500 revolutions per minute, and the spin coating time is 30 to 60 seconds to ensure uniform coating thickness and good adhesion.
8. The method for preparing a high thermal conductivity and high insulation polymer-based composite material according to claim 4, characterized in that: In the molding step, the hot pressing molding pressure is controlled at 8 to 12 MPa, and the molding time is 5 to 15 minutes to ensure that the filler inside the composite material is evenly distributed and the interface is tightly bonded.
9. A method for preparing a high thermal conductivity and high insulation polymer-based composite material according to claim 4, characterized in that: In the melt blending step, the mixed material needs to be dried in a vacuum drying oven at 100 to 150 degrees Celsius for 2 to 4 hours to remove volatile impurities and moisture in the material.
10. The method for preparing a high thermal conductivity and high insulation polymer-based composite material according to claim 4, characterized in that: The calcined flaky boron nitride filler needs to be screened to ensure that the filler size is evenly distributed, and the particle diameter deviation is controlled within ±10%. The screening uses airflow screening equipment or ultrasonic vibration screening equipment, wherein the airflow screening equipment is suitable for fillers with a smaller particle size range, and the ultrasonic vibration screening equipment is suitable for fillers with a larger particle size. Both ensure screening efficiency and uniformity of particle distribution.
Citation Information
Cited By
Gradient composite solid electrolyte, preparation method and in-situ interface repair structure
CN120600907A